Mentoring for urologists. (March 2019) - Terry, Tim; Redfern, Nancy; French, Gordon
Trainee and established urologists are familiar with 'generic mentoring' as a potpourri of helping aids that include supervision, coaching, buddying, career advice, counselling and patronage to enable mentees to develop professionally. However, most are unfamiliar with 'developmental mentoring' as a highly specific learnt technique through which mentors help mentees, by interactive dialogue, to choose their own agendas and arrive at their own solutions to career/professional/personal opportunities or difficulties as distinct from the paternalistic mentor approach typified by the downward flow of information generated by 'generic mentoring'. This paper is a systematic review of developmental mentoring as pertains to urologists in the UK, and reports outcomes of 1-hour taster sessions between Egan-trained mentors and urologists offered at British Association of Urological Surgeons (BAUS) annual general meetings since 2013. Both the General Medical Council and the Royal College of Surgeons of England imply that 'mentoring' is mandatory for both trainees and trained urologists, but fail to clarify what they mean by a 'mentor', which potentially creates a void in providing 'developmental mentoring' since the later requires specific training and is costly to provide. Currently, most 'developmental mentoring' is performed by trained staff in Local Education and Training Boards or National Health Service Trusts. BAUS has an opportunity to offer 'developmental mentoring' through a portal on its website to manage opportunities and difficulties experienced by its members. Level of evidence: This paper is a systematic review as pertains to the place of mentoring in current urological practice. By its nature, it has reviewed previous narrative reviews and its highest level of evidence is a contemporary paper from 2016, which was a comparative cross-sectional study; other case series were reviewed. Overall, this amounts to level 4 with a recommendation of C as per the Oxford Centre for Evidence-based Medicine Levels of Evidence.